(untitled) (Revista Apotheke, 2021)
I propose to unite visual arts and literature in this essay to think about translations made by black authorship. As the result of a linguistic provocation, I seek to emerge oriented translations (as in the metaphysical concept of the Yoruba word ori), as well as to discuss new imaginaries that compose the artistic-literary field today. Therefore, Beatriz Nascimento, Yhuri Cruz, Rosana Paulino, and Conceição Evaristo are people who use an oriented translation based on directions related to an ethnic-racial, political and gender dialogue.